DETERMINANTS OF INVESTMENT OPPORTUNITIES IN PHARMACEUTICAL COMPANIES REGISTERED ON THE IDX DURING THE COVID-19 PANDEMIC - H. Adam Afiezan; Meidarti Gea; Roma Gunarty Pakpahan; Keulana Erwin (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The reason of this exposition is to form a judgment, whether it is concurrent or fractional. Deals Development, Gaining Development, Resource Development, and Return On Speculation (ROI) to Speculation Opportunity Set (IOS) in Pharmaceutical sub-sector companies recorded on the Indonesia Stock Exchange (IDX) in 2019Q1–2021. With the assistance of a method called 'linear induction analysis' which takes under consideration 'normality', 'multicollinearity', 'autocorrelation' and 'heteroscedasticity'. The comes about of the F test examination appear that the Fcount esteem is 2.910282 higher than the Ftable esteem of 2.58, and a critical esteem is 0.0320370.05 which suggests that the ROI is essentially higher than the Ftable esteem with regard to Venture Opportunity Set (IOS) . Given that the R Square is around 0.1373, this shows a 13.73% speculation opportunity set, concurring to the coefficient of assurance